PENERAPAN TARI KREATIF DENGAN EKSPLORASI IMAGERY LINGKUNGAN HIDUP ANAK USIA DINI - arni apriani (EARLY CHILDHOOD : JURNAL PENDIDIKAN, 2017)
Abstract Early childhood is an individual figure who is always active, enthusiastic, and curious about what is seen, heard, felt. They never stop to explore, learn and easy to absorb information. They have feelings that are formed by the situation (happy, sad, angry, disappointed, appreciated, and so on). This is the time when they need friends to play with the socio-cultural environment where he is. In early childhood education must relate to the value of art, beauty and harmony that leads to happiness in the child's life according to the cultural roots in which they live (aesthetics) as well as the religious values ??it embraces. The concept of learning: learning while playing, doing, through stimulation, with the core experience of exploring the social environment of culture, which produces knowledge and understanding by observing, imitating and experimenting. Environmental exploration for early childhood is important because they are excellent explorers. Creative dance with the exploration of environmental imagery can provide an aesthetic experience, learning experience, social experience, and can foster children's creativity to explore the elements of dance.